1985
DOI: 10.1038/314098a0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-2 receptors as a differentiation marker on intrathymic stem cells

Abstract: The thymus is regarded as the primary site for T-cell lymphopoiesis, but very little is known about the lineage inter-relationships of cells within that organ. At least four subpopulations of mouse thymocytes can be defined on the basis of staining with monoclonal antibodies directed against the T-cell differentiation antigens Lyt-2 and L3T4 (ref. 2). Thus immunocompetent (medullary) thymocytes, like peripheral T cells, express either Lyt-2 (cytotoxic phenotype) or L3T4 (helper phenotype) but not both, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
239
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(243 citation statements)
references
References 27 publications
4
239
0
Order By: Relevance
“…The current data indicate that rat T-cell precursors (TN cells) express IL-2 receptors, a fact previously denied by other authors (Takacs et al, 1988;Kampinga and Aspinall, 1990), although repeatedly reported in mice, chickens, and humans (Ceredig et al, 1985;Toribio et al, 1989;Fedecka-Brunner et al, 1991). In agreement with our results, Brocke et al (1987) found IL-2Rce-beating cells in the thymus of 16-day-old fetal rats.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current data indicate that rat T-cell precursors (TN cells) express IL-2 receptors, a fact previously denied by other authors (Takacs et al, 1988;Kampinga and Aspinall, 1990), although repeatedly reported in mice, chickens, and humans (Ceredig et al, 1985;Toribio et al, 1989;Fedecka-Brunner et al, 1991). In agreement with our results, Brocke et al (1987) found IL-2Rce-beating cells in the thymus of 16-day-old fetal rats.…”
Section: Discussionsupporting
confidence: 83%
“…However, much controversy has arisen concerning its role, if any, in the first stages of T-cell development. The expression of individual chains (or,/3, and y) of the IL-2 receptor (IL-2R) on immature thymocytes (Ceredig et al, 1985;Toribio et al, 1989;Kondo et al, 1994;Reya et al, 1996), as well as the ability of these cell subsets to produce IL-2 (Tentori et al, 1988b;Zlotnik et al, 1992) and proliferate in its presence (Ceredig et al, 1989;Toribio et al, 1989;Brooks et al, 1993), *Corresponding author. support the idea that IL-2 may drive the proliferation and the differentiation of T-cell precursors. In fact, the culture of T-cell progenitors with IL-2 promotes their differentiation to TcRcq3, TcRy6, and NK cells (Toribio et al, 1988;De la Hera et al, 1989;Brooks et al, 1993;He and Kabelitz, 1995), and in vivo or in vitro treatments that alter the IL-2/IL-2R complex profoundly modify the T-cell maturation (Jenkinson et al, 1987;Skinner et al, 1987;Tentori et al, 1988a;Plum et al, 1990;Waanders and Boyd, 1990;ZufiigaPflticke and Kruisbeek, 1990;Kroemer et al, 1991;Maslinski et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, TN thymocytes at days 14 and 15 of fetal development have been shown to express mRNA for Iblj3, IL4, II.-5, IL-6, II.-7, IFN-3,, and TNF (7)(8)(9). Also expressed are the cell surface molecules: Thy-1, CD2, CD16, CD44, heat stable antigen (HSA), thymic shared antigen (TSA-1), CD18 (LFA-1), CD54 (ICAM-1), Ly-6, CD26 (THAM-1) and the cx chain of the II.-2 receptor (CD25) (10)(11)(12)(13)(14)(15)(16)(17). Markers such as CD25, ICAM-1, CD44, and Ly-6 are prominent on mature T lymphocytes only after TCR activation (15,18,19).…”
mentioning
confidence: 99%
“…The MoAbs used were: rat anti-mouse CD8+ (originally from Dr R. Fitch, UniversityofChicago. USA), rat anti-mouse CD4 (25) and anti-mouse Thy 12 (F7D5 clone. Bicester, Oxon, UK).…”
Section: In Vitro Depletion Of T Lymphocyte Subsets and Adoptive Tranmentioning
confidence: 99%